2021
DOI: 10.1111/jrh.12571
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life in head and neck cancer survivors: Evaluating the rural disadvantage

Abstract: Purpose Head and neck cancer (HNC) survivors often experience distress and health‐related quality of life (HRQOL) impairment. Research suggests that rural cancer patients may have poorer outcomes than urban patients. This study examined whether HNC patient emotional and HRQOL outcomes differ in those living in a rural versus urban location at 6 and 12 months postdiagnosis. Methods A total of 261 HNC patients were included from a longitudinal study of HNC outcomes. The majority were diagnosed with advanced stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 60 publications
2
15
0
Order By: Relevance
“…13 In a recent study of psychosocial outcomes in rural HNC patients, it was reported that rural patients experienced greater levels of depressive symptomatology and poorer HNC-specific HRQOL when compared to urban HNC patients. 14 These studies align with a larger body of evidence suggesting that outcomes, including survival, are worse among rural cancer patients of all types including breast, gynecologic, prostate, colorectal, lung, melanoma, hematologic, and HNCs [15][16][17][18][19][20] and may be exacerbated by problem alcohol use. Some work in chronic disease populations has suggested that the presence of factors that negatively impact quality of life and disease management may explain why patients in rural settings face a so-called "rural disadvantage".…”
Section: Introductionsupporting
confidence: 60%
See 4 more Smart Citations
“…13 In a recent study of psychosocial outcomes in rural HNC patients, it was reported that rural patients experienced greater levels of depressive symptomatology and poorer HNC-specific HRQOL when compared to urban HNC patients. 14 These studies align with a larger body of evidence suggesting that outcomes, including survival, are worse among rural cancer patients of all types including breast, gynecologic, prostate, colorectal, lung, melanoma, hematologic, and HNCs [15][16][17][18][19][20] and may be exacerbated by problem alcohol use. Some work in chronic disease populations has suggested that the presence of factors that negatively impact quality of life and disease management may explain why patients in rural settings face a so-called "rural disadvantage".…”
Section: Introductionsupporting
confidence: 60%
“…35 The BDI consists of 21 items scored 0-3, each assessing a unique category of depressive symptoms. Cut-off scores have been established which suggest minimal (0-9), mild (10)(11)(12)(13)(14)(15)(16)(17)(18), moderate (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29), and severe depression. 35 The BDI has been used in both nonclinical and clinical samples, including those with HNC.…”
Section: Measurement Of Key Variablesmentioning
confidence: 99%
See 3 more Smart Citations